Back Cover: Tailoring Large Pores of Porphyrin Networks on Ag(111) by Metal–Organic Coordination (Chem. Eur. J. 43/2016). Issue 43 (31st August 2016) - Bischoff, Felix; He, Yuanqin; Seufert, Knud; Stassen, Daphné; Bonifazi, Davide; Barth, Johannes V.; Auwärter, Willi
Abstract : A two‐dimensional metal–organic coordination network is featured on the back cover, showing an experimental scanning tunneling microscopy (STM) image and the corresponding structural model. The network is based on cyano‐functionalized porphyrins featuring fourfold coordination to Cu centers. This STM study is complemented by Monte Carlo simulations and elucidates the role of cyano and pyridyl termini and Cu centers for engineering of molecular architectures on a silver support. More information can be found in the Full Paper by D. Bonifazi, W. Auwärter et al. onpage 15298 ff.